Peran Seminar Public Speaking Dalam Meningkatkan Rasa Kepercayaan Diri Bagi Siswa SMK 3 PGRI Kota Serang - Heru Winarno; Syaina Ulfah A; Isma Istiqomah; Gisela Tri Wibowo; Devina Gita Amelia (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
Abstract: Public speaking is a person's ability to speak in public clearly, confidently, and effectively. It involves the ability to convey a message or information to an audience in a way that can be understood and motivates them. Public speaking skills involve several key elements, including the ability to plan and structure presentation materials well, organize thoughts logically, use supportive body language and facial expressions, and manage any nervousness or anxiety that may arise. The purpose of holding a public seminar is to convey information, influence, express opinions, motivate, entertain and promote self-confidence where self-confidence is a quality that a person has and believes in his abilities. Confidence is very useful when we are speaking in front of many people.